PERAN GURU PENDAMPING KHUSUS DALAM PENDIDIKAN INKLUSI DI TK VIEDU INKLUSI TEMBILAHAN - Wina Santyani; Khamim Zarkasih Putro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education provides opportunities for children with special needs (ABK) to learn together in the same school environment. In the context of early childhood education, the role of Special Assistant Teachers is very important in supporting the successful implementation of inclusive learning. This study aims to describe the role of Special Assistant Teachers at Viedu Inklusi Tembilahan Kindergarten in the learning process of children with special needs. The method used is qualitative descriptive with data collection techniques through interviews and observations of classroom teachers and Special Assistant Teachers. The results of the study show that Special Assistant Teachers at Viedu Inklusi Tembilahan Kindergarten play the role of facilitators, companions, and mediators in the learning process. Special Assistant Teachers focus on providing stimulus in the aspects of fine motor, gross motor, and children's social skills. Special Assistant Teachers also set developmental indicators that are tailored to each child's abilities, as well as bridge communication between classroom teachers and parents. This strategic role supports the achievement of optimal development of children with special needs, while easing the burden on classroom teachers in the implementation of inclusive learning.